(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores stylistic features, pictorial expression and the skill of using tools in the novel “The Three Brothers” by the great German writer Erich Maria Remarque. The scale of the themes reflected in the work, the world of heroes are widely covered. The writer’s skill in illuminating the inner world of the characters has been studied. The importance of the novel in the development of 20th century Uzbek prose is shown. It is proven that the idea of condemning the war in the work is shown through the description of the characters’ difficult and tragic fate and spiritual experiences.